Altruisme dan Keterlibatan Akademik pada Mahasiswa: Peran Psychological Well-Being sebagai Variabel Mediator - Fuadah, Luk Luk Atul; Nainggolan, Eben Ezer; Muslikah, Etik Darul (JIWA: Jurnal Psikologi Indonesia, 2025)
The problem in this study was identified as the low level of academic engagement in students in Surabaya, which is thought to be influenced by altruism, with the role of psychological well-being as a mediator that is expected to be able to strengthen or explain the relationship, so that researchers conducted a study that attempted to see the relationship between Altruism and Academic Engagement and Psychological Well-Being as a mediator with the aim of exploring the complex relationship between altruistic behavior, psychological well-being, and academic engagement of students. The respondents of this study were 384 active students in Surabaya. The analysis technique used was mediation analysis with the help of JASP. The results showed that Altruism had a relationship with Academic Engagement of 56.3 with a significance level of 0.001 (p<0.05). The mediation test showed that Psychological Well-Being was able to mediate the relationship between Altruism and Academic Engagement from the indirect effect having a Z-value of -14.7 with a significance level of less than 0.001 which stated that Psychological Well-Being was able to partially mediate the relationship between altruism and academic engagement.